Carta de Horace Towner a Roberto H. Todd - Todd, Roberto H.; Towner, Horace M. (My University, 1920)
Carta relacionada a visita a Islas Vírgenes de una Comisión del Congreso
Keywords: Islas Vírgenes; United States. Congress. House. Committee on Interior and Insular Affairs